LE CRETACE SUPERIEUR DE LA REGION D’IMIN’TANOUT (HAUT ATLAS OCCIDENTAL, MAROC) : SEDIMENTOLOGIE, BIOSTRATIGRAPHIE ET ANALYSE SEQUENTIELLE - Algouti, Ahmed; Algouti, Abdellah; Hadach, Fatiha (European Scientific Journal, ESJ, 2015)
The sedimentological and biostratigraphic study of Upper Cretaceous in the region of Imin'Tanout allowed to individualize three differents senonians formations: The dolomitic limestone and marl formation of Anou-nfeg of Coniacien age, the dolomitic formation of Ait Abbes of Santonian age and the phosphatic formation of Maastrichtian age. The first formation is formed in an environment of internal platform in communication with the wide passing a coastal environment with continental influences. The second formation characterizes a tidal internal platform passing an environment of sebkha type, affected by marine incursions. The last formation is transgressive and marks the return of the sea, in a hot and arid climate.